Pleiotrophin is a driver of vascular abnormalization in glioblastoma. (1st November 2016) - Zhang, Lei; Dimberg, Anna
ABSTRACT: In a recent report by Zhang et al., pleiotrophin (PTN) was demonstrated to enhance glioma growth by promoting vascular abnormalization. PTN stimulates glioma vessels through anaplastic lymphoma kinase (Alk)-mediated perivascular deposition of vascular endothelial growth factor (VEGF). Targeting of Alk or VEGF signaling normalizes tumor vessels in PTN-expressing tumors.